The relationship between the home literacy environment and the development of emergent literacy skills in Palestinian preschoolers in Lebanon. (c2017) - Hammad, Beesan Ibrahim (2017)
Literacy acquisition can be best thought of as a developmental continuum, rather than an all-or-nothing phenomenon, that originates early on in a children’s lives before they start formal schooling. How and how often parents expose their children to literacy before entering school is vital for later literacy development. This is especially important in Palestinian children facing multiple risk factors. As a result, the home literacy environment is recognized as an important setting for children to observe others’ literacy behaviors and engage in direct and indirect literacy activities with others. Researchers hypothesize that parental teachings and storybook exposure promote emergent literacy and language skills respectively. This study used correlational analysis to examine the relationship between the different aspects of the home literacy environment using the Home Literacy Environment Questionnaire (HLEQ) and the emergent literacy and language skills of Palestinian refugee children living in Burj El-Barajneh camp. Emergent literacy and language skills were measured using Teacher Rating of Oral Language and Literacy (TROLL) and the Dynamic Indicators of Basic Early Literacy Skills (DIBELS). The study also aimed at demonstrating the extent to which preschool enrolment and parents’ educational levels correlate with the home literacy environments and children’s emergent literacy and language performance. The study found that the correlation between parental literacy teaching and emergent literacy skills indicates that indirect reading activities have a larger effect on the emergent literacy skills than direct ones. This has significant implications for the role of parental involvement in children’s education. Future research should consider the quality of preschool education, the emotional quality of adult-child interactions, and Palestinian refugees residing outside of refugee camps to draw better conclusions.